Hubungan Kadar Gula Darah Wanita Hamil Dengan Gingivitis - Henggardy Hanggono, Mohammad; , drg. Ana Riolina, MPH; , Drg. Suyadi (2016)
Background: pregnancy can influence general health and oral health, especially periodontal tissue. Gingivitis was gingival inflamatoryy that caused by increased of estrogene and progesterone homone during pregnancy. Increased of estrogene and progesterone homone during pregnancy caused gingival more sensitive often inflamation. This situation can be aggravated by high of blood sugar. Purpose: this study aimed was to know influence of blood sugar to the severity of gingivitis in pregnant women at Puskesmas Moropelang. Method: this study was analytic observational with cross sectional method that held on 1 August 2016. Sampling technique used total sampling method so it can be obtained 35 pregnant women who want to be subject. The severity of gingivitis obtained using Gingival Index (GI) examination. Pregnant women's score of casual plasma glucose taken during visit at Poli KIA KB Puskesmas Moropelang. Data tested using crosstabulation and kolmogorov-smirnov with confidence interval 95% to know the relation between the severity of gingivitis and blood sugar in pregnant women. Result: data that obtained showed that the group of pregnant women that has normal blood sugar experiencce mild gingivitis 83%, moderate gingivitis 14% and severe gingivitis 3% while pregnant women that has high blood sugar no one that experiencce mild gingivitis, moderate gingivitis 33%and severe gingivitis 67%. Result of kolmogorov-smirnov p=0,002 (p<0,05). Conclusion: it can be concluded that there was relation between the severity of gingivitis and blood sugar in pregnant women in Puskesmas Moropelang. st March until 30 th